Struktur dan Makna Tarian Yosakoi - Khairunnisa, Yussy Talitha; Rahayu, Ely Triasih; Kadafi, Muammar (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang, 2022)
The purpose of this study was to determine the structure and meaning of movements contained in the yosakoi dance. The yosakoi dance is a traditional dance that was first introduced in 1954 in Kochi prefecture. The kochi yosakoi dance was first performed in a summer festival, with the basic dance was called seicho. Seicho yosakoi is danced with the yosakoi naruko odori song and uses a musical instrument called naruko. Besides at Kochi prefecture, yosakoi also has expanded to the Hokkaido area. Yosakoi dance in Hokkaido is known as yosakoi soran. Yosakoi soran was first created by Hasegawa Gaku in 1992. Different from kochi yosakoi, yosakoi soran was first introduced with the traditional song soran bushi. The type of this study was descriptive qualitative. The data source of this study was the movement of yosakoi dancers, namely the Iroha and Yuujou Taiko groups. The method of this study used literature study, observation and interview. The data analysis technique was conducted by analyzing the movement structure and meaning of the seicho and soran bushi dances based on the semiotic concept of Roland Barthes. The results of this study showed that there were 5 movement structures in the seicho yosakoi dance that contained connotative meanings, and there were 14 movement structures in the soran bushi dance. The conclusion from the structure and meaning of these two dances are that they only have connotative meanings.  In the seicho dance, it contains the meaning of an invitation for people to come and have fun during the summer at the yosakoi festival. While in soran bushi, this dance has the meaning of describing how fishermen go to sea to catch fish.